The Characteristics Of Physico-Chemical Quality And The Sensory Evaluation Of Kesambi Jam (Schleichera Oleosa, Merr) - Rahmawati Saleh; Syahriati, Syahriati; Nur Fitriani UA; Imran Muhtar; Andi Ridwan Makkulawu (International journal of technology and education research, 2023)
Kesambi is one of the fruit plantations in Indonesia that almost extinct. This fruit has similar texture, colour, and sweet-sour taste with longan. However, there is still limited research on the ripe Kesambi in processed food products as the main ingredient of jam in order to obtain higher economic value. This research aims to examine the sensory evaluation and characterize the quality of kesambi jam with treatment cooking duration and sugar addition. The research was conducted at the Quality Management Laboratory, Pangkep State Agricultural Polytechnic and at the Nutrition Laboratory, Faculty of Animal Husbandry, Hasanuddin University. The duration of cooking conducted in 3 levels: 20 minutes, 25 minutes and 30 minutes; and the addition of sugar also with 3 levels of concentration: 20%, 25% and 30%. While testing the quality characteristics of kesambi jam included physical (viscosity), chemical (moisture content, total soluble solid, and vitamin C,) and organoleptic tests (color, flavour and taste). The results of the characterization showed that the viscosity of kesambi jam ranged from 68.91- 76.15 cP. The moisture content of kesambi jam decreases with increasing cooking time and sugar concentration. Total soluble solids range from 63.3 – 71.65 °brix. The average content of vitamin C. ranges from 16.74 – 18.25 mg / 100 g of ingredients. The panelists' acceptance of the color, flavour and taste of kesambi jam, on average, response with a favorable score range of 5.31 to 6.1. Based on the organoleptic test, the best treatment of this research was on the additional sugar of 30% with a cooking duration of 30 minutes.